Free Will and Neuroscience: From Explaining Freedom Away to New Ways of Operationalizing and Measuring It - Lavazza, Andrea (Frontiers in Human Neuroscience, 2016)
The concept of free will is hard to define, but crucial to both individual and social life. For centuries people have wondered how freedom is possible in a world ruled by physical determinism; however, reflections on free will have been confined to philosophy until half a century ago, when the topic was also addressed by neuroscience. The first relevant, and now well-known, strand of research on the brain correlates of free will was that pioneered by Benjamin Libet (Libet et al., 1983), which focused on the allegedly unconscious intentions taking place in decisions regarded as free and voluntary. Libet’s interpretation of the so-called readiness potential (RP) seems to favour a sort of deflation of freedom (Soon et al., 2008). However, recent studies seem to point to a different interpretation of the readiness potential, namely that the apparent build-up of the brain activity preceding subjectively spontaneous voluntary movements may reflect the ebb and flow of the background neuronal noise, which is triggered by many factors (Schurger et al. 2016). This interpretation seems to bridge the gap between the neuroscientific perspective on free will and the intuitive, commonsensical view of it (Roskies, 2010b), but many problems remain to be solved and other theoretical paths can be hypothesised. The paper therefore proposes to start from an operationalizable concept of free will (Lavazza and Inglese, 2015) to find a connection between higher order descriptions (useful for practical life) and neural bases. This new way to conceptualize free will should be linked to the idea of “capacity”: that is, the availability of a repertoire of general skills that can be manifested and used without moment by moment conscious control. The capacity index, which is also able to take into account the differences of time scales in decisions, includes reasons-responsiveness and is related to internal control, understood as the agent’s ownership of the mechanisms that trigger the relevant behaviour. Cognitive abilities, needed for one to have capacity, might be firstly operationalized as a set of neuropsychological tests, which can be used to operationalize and measure specific executive functions, as they are strongly linked to the concept